A centurial development of the North Sea fish megafauna as reflected by the historical Swedish longlining fisheries. Issue 3 (3rd February 2014) - Cardinale, M; Bartolino, V; Svedäng, H; Sundelöf, A; Poulsen, R T; Casini, M
Abstract Historically, to compensate for declining catches, fishers have usually shifted from species characterized by high catch rate onto less easily caught species or have moved into new fishing grounds. Such shifts are poorly documented for areas with a long history of exploitation (i.e. North Sea) as they occurred long time before the start of the regular assessments of the marine resources. The Swedish longline fisheries in the Kattegat‐Skagerrak and North Sea have a long history that spans over several centuries. These fisheries have historically targeted large demersal predator fish as ling (Molva molva), cod (Gadus morhua), Atlantic halibut (Hippoglossus hippoglossus) and skates (mainly Dipturus spp.). In this study, data from the Swedish longline fisheries from 1859 to 1960 have been collated. The data show that the geographical expansion of the fishery was extensive. At the turn of the 20th century, offshore longlining became concentrated north and west of the Shetlands and Hebrides, and after the WWII, the fishery expanded to Iceland and Rockall. In the offshore fishery, CPUE for the main target species, ling, remained stable, whereas for the other species, with the exception of tusk (Brosme brosme), CPUE showed a dramatic decline over time. In contrast, in the coastal longlining fishery, severe declines were revealed for all major target species except cod. We argue that the constant search for new fishing grounds in the Northeast Atlantic reflects a dwindling resource, where the fishermen kept the catch rates of ling high by travelling to more and more distant fishing grounds.